DIVERSIFIKASI PAKET STAYCATION HOTEL KAWASAN TUBAN, KABUPATEN BADUNG, BALI DI MASA PANDEMI COVID-19 - Nelsye Lumanauw; Gst. Bgs. Wirya Gupta (Fakultas Pariwisata Universitas Pancasila, 2022)
ABSTRACT The hotel industry is taking advantage of the Covid-19 pandemic situation by creating staycation packages to maintain business. Policy of restricting employees and opening facilities resulted in a mismatch between product diversification efforts and the actual condition of the hotel and the expectations of tourists doing staycation activities. The analysis of the diversification of staycation hotel packages in the Tuban, Badung, Bali area and its implementation are the purpose of this study. The research method qualitative descriptive analysis was used in this study to analyze the staycation hotel packages in the Tuban, Badung, Bali area which became the object of this research, namely The Patra Bali Resort & Villas, Rama Beach Resort & Villas, Quest Hotel Kuta by Aston, Hotel Sulis Beach & Spa. The theory of Resources Based View is used to analyze superior hotel products that are packaged into staycation packages. Diversification theory is used to analyze the implementation of staycation packages at hotels, supported by tourist reviews both online and offline. The conclusion of this study is that the staycation trend in the midst of the Covid-19 pandemic shows a shift in the pattern of traveling by the community. However, the hotel must try to optimize the existing employees, so that the hotel's brand image remains good. Keywords: product diversification, staycation, Covid-19 pandemic